Students’ Academic Engagement in Secondary Schools: Parental Involvement and Academic Resilience as Predictor Variables - Anierobi, Elizabeth Ifeoma; Nwikpo, Mary Nneka; Okeke, Nkechi Uzochukwu; Ezennaka, Anthony Obinna (MultiTech Publisher, 2024)
Academic engagement is essential if students must fulfil their academic goals and key to their success. The research employed a correlational research design to assess the extent to which parental involvement and academic resilience can predict the academic engagement of secondary school students in Anambra State. The study was guided by three research questions and tested three null hypotheses at a significance level of 0.05. 19708 senior secondary class two (SS2) students made up the study's population, from which 960 samples were selected using a multi-stage simple random approach. The study employed three instruments, namely the Parental Involvement Questionnaire (PIQ), Academic Resilience Questionnaire (ARQ), and Academic Engagement Questionnaire (AEQ), which were validated by three experts in the field of Educational Psychology. To evaluate the instruments' reliability, the Cronbach Alpha technique was employed, yielding alpha coefficients of 0.72, 0.71, and 0.70 for PIQ, ARQ, and AEQ, respectively. Simple regression analysis was used to test the null hypothesis and simple correlation analysis was used to answer research questions. The results showed that academic engagement is positively correlated with parental involvement and academic resilience. It also demonstrated that parental involvement and academic resilience worked together to enhance secondary school students' academic engagement in Anambra State. The study's conclusions led to the recommendation that parents get active in their children's education to both strengthen their resilience and raise their academic engagement.